Rod photoreceptor ribbon synapses in DBA/2J mice show progressive age-related structural changes. - Fuchs, Michaela; Scholz, Michael; Sendelbeck, Anna; Atorf, Jenny; Schlegel, Christine Julie; Enz, Ralf; Brandstätter, Johann Helmut (PLoS ONE, 2012)
The DBA/2J mouse is a commonly used animal model in glaucoma research. The eyes of DBA/2J mice show severe age-related changes that finally lead to the degeneration of retinal ganglion cells and the optic nerve. Recent electroretinogram studies identified functional deficits, which suggest that also photoreceptor cells are involved in the pathological processes occurring in the DBA/2J mouse retina. In a comparative study, we examined anatomical and molecular changes in the retinae of DBA/2J and C57BL/6 control mice with light and electron microscopy and with PCR analyses. In the retina of the DBA/2J mouse, we found a thinning of the outer plexiform layer, the first synaptic layer in the transfer of visual signals, and age-dependent and progressive degenerative structural changes at rod photoreceptor ribbon synapses. The structural ribbon changes represent a photoreceptor synaptic phenotype that has not yet been described in this animal model of secondary angle-closure glaucoma. Furthermore, genes of the classical complement cascade were upregulated in the photoreceptor cells of aging DBA/2J mice, suggesting a putative link between ribbon synapse degradation and the innate immune system. © 2012 Fuchs et al.
UnivIS-Import:2015-04-14:Pub.2012.med.IB.profes_1.rodpho